Unconscious Gods and the Return of Belief in Max Gladstone's Craft Sequence - Melville, Peter (Journal of religion and popular culture, 2021)
This article considers the role of belief in Max Gladstone's Hugo-nominated Craft Sequence, a six-volume fantasy series that imagines a world in which humanity's gods have either expired or been resurrected in a zombie-like state so that their divine power can be siphoned and used to fuel the social, economic, and technological superstructure of everyday modern life. The article draws on the work of Slavoj Žižek, Jacques Lacan, and Alain Badiou to show how Gladstone portrays the return of belief as an effective vehicle for social change that counters a model of atheism in which the individual’s supposed liberation from God entails the repression of its continued commitment to what Lacan calls the big "Other," which is to say, the symbolic order itself.